Dynamics of Kidney Function in Patients with Chronic Kidney Disease and Atrial Fibrillation Who Receive Dabigatran - N. A. Novikova; Z. K. Salpagarova; M. I. Chashkina; A. A. Bykova; Z. A. Alimova; А. S. Yadykina; D. F. Mesitskaya; N. A. Babakova; D. A. Andreev (Столичная издательская компания, 2021)
Atrial fibrillation (AF) is the most frequent type of supraventricular arrhythmias. The anticoagulant therapy should be prescribed to prevent thromboembolic events. According to randomized clinical trials, anticoagulants do not always prove their high efficiency in the real clinical practice. It is a complicated issue for any doctor to prescribe the anticoagulant therapy for patients with AF and CKD. 30 % of patients with atrial fibrillation are known to have chronic kidney disease, while 10-15% of patients with chronic kidney disease are diagnosed with atrial fibrillation. Currently, there are scarce studies into the use of direct oral anticoagulants in patients with atrial fibrillation and chronic kidney disease (in case of Glomerular Filtration Rate (GFR) below 45 ml/min/1.73 m2).Aim. To determine the dynamics of GFR in patients with AF and CKD (in case of GFR below 45 ml/min/1.73 m2).Material and Methods. The sub-analysis was carried out to examine a single-centre prospective study into the optimization of the anticoagulant therapy in the outpatient practice. Initially, 133 dabigatran taking patients were enrolled in the study, and 79 patients were included in the final analysis. Endpoints were changes in Glomerular Filtration Rate (CKD-EPI) formulae as of the inclusion date, in 6, 12, 24 and 60 months after the inclusion. Changes in the renal function shall mean a decrease or increase in GFR by ≥5 ml/min.Results. The average follow-up period for patients was 1785 ± 218 days. A GFR>45 ml/min/1.73 m2 occurred in 116 (87.2%) patients, and a GFR <45 ml/min/1.73 m2 was found in 17 (12.8%) patients. The average HAS-BLED score was 1.8, and CHA2DS2VASc score - 3.8. During the observation period, there were 3 cases of major bleeding and 133 cases of minor bleeding. Both major (р=0.025) and minor (р=0.012) bleeding were statistically significant more frequent in patients with GFR below 45 ml/min. During 5 years of follow-up, 66 (49.6%) patients had an average decrease in GFR of 3.32 ml/min/1.73 m2 per year. Patients with the initially declined GFR (below 45 ml/min) did not demonstrate a significant dynamic of the renal function during the dabigatran therapy. The mortality rate in this group during the observation period was 61.5%.Conclusion. In 49.6% of patients during 5 years of follow-up, GFR decreased by an average of 3.32 ml/min/1.73 m2 per year, which does not exceed the indicators typical for patients with cardiovascular events and CKD.